Shear connection performance of cold-formed steel and plywood composite flooring systems: Experimental and numerical investigation. (February 2023) - Al-Hunaity, Suleiman A.; Karki, Dheeraj; Far, Harry
Abstract: This study carries out numerical and experimental investigation on shear connection performance of flooring systems comprising of cold-formed steel joists and engineered plywood panels. A 3-D finite element model has been developed using ANSYS software which considers the nonlinear behaviour and damage of plywood panels using a maximum stress-based criterion incorporated in the FE model. The yielding behaviour of steel joists and fasteners (screws and bolts) is defined as a multilinear plastic hardening material model defined in ANSYS software. The FE model was validated against the experimental results obtained from push-out tests conducted on specimens utilising different connection arrangements. The validated FE models showed a good agreement with the experimental results of the push-out tests in terms of load-slip behaviour, ultimate peak capacity, and failure modes. Finally, the validated FE models are utilised to perform a parametric study that investigates the effect of varying various parameters, including diameter and yield strength of self-drilling screws, the thickness of plywood panels, value of friction coefficient, and the ratio of fastener diameter to the joist thickness, on the initial stiffness, failure mode and ultimate load capacity of the cold-formed steel and plywood composite connections.